PEMBANGUNAN KOTA PALEMBANG DENGAN KONSEP TATA RUANG KOTA HIJAU PADA MASA HINDIA-BELANDA - Maryani Sujiyati; Nor Huda Ali (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2015)
Palembang is one of the old city in Indonesia. Viewed from the side of the urban morphology of the city is constantly changing following the development policy carried out by the authorities. When the empire, the pattern of Palembang follow the pattern of the flow stream that is widely available in Palembang. However, these conditions expansion changed when the Dutch East Indies government control of the city and make Palembang as the capital of Palembang residency. At this time the colonial government began to organize and develop the city of Palembang in the spatial concept of green. This kind of historical study is expected to be a reference in building Palembang forward. Urban development should not be destructive to the existing city, but also need to consider the social and cultural sustainability. Eliminating the historical legacy of the past, it means eliminating the national identity. If this happens, it means that nation to extinction.